A 60 pW gmC Continuous Wavelet Transform Circuit for Portable EEG Systems - Casson,AJ; Rodriguez-Villegas,E (IEEE Journal of Solid-State Circuits, 2011)
This paper presents a low power, low voltage and low frequency bandpass filter implementation of a continuous wavelet transform (CWT) for use with physiological signals in the electroencephalogram (EEG) range (1–150 $mu$V, 1–70 Hz bandwidth). Experimental results are presented for a 1 V, 7th order g$_{m}$ C filter based CWT with filter center frequencies ranging from 1 to 64 Hz.